2009
DOI: 10.5194/npg-16-607-2009
|View full text |Cite
|
Sign up to set email alerts
|

The stochastic multiplicative cascade structure of deterministic numerical models of the atmosphere

Abstract: Abstract.By direct statistical analysis we show that over almost all their range of scales and to within typically better than ±1%, atmospheric fields obtained from analyses and numerical integrations of atmospheric models have the multifractal structure predicted by multiplicative cascade models. We quantify this for the horizontal wind, temperature, and humidity fields at 5 different pressure levels for the ERA40 reanalysis, the Canadian Meteorological Centre Global Environmental Multiscale (CMC, GEM) model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 61 publications
3
53
0
1
Order By: Relevance
“…There have been attempts to examine the scaling of model fields, both on a case-study basis as described above and more generally. Lovejoy et al (2009c) and Stolle et al (2009) concluded that weather could be modelled as a cascade process, pointing out that whereas horizontal scaling could be investigated for models with regularly spaced grids, the general absence of such regularity with altitude in atmospheric models used for assimilation and forecasting hampered analysis of their vertical scaling. In this case, the cascades refer to the meaning whereby the same processes are at work scale by scale across the whole scaling range…”
Section: Some Considerations For Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been attempts to examine the scaling of model fields, both on a case-study basis as described above and more generally. Lovejoy et al (2009c) and Stolle et al (2009) concluded that weather could be modelled as a cascade process, pointing out that whereas horizontal scaling could be investigated for models with regularly spaced grids, the general absence of such regularity with altitude in atmospheric models used for assimilation and forecasting hampered analysis of their vertical scaling. In this case, the cascades refer to the meaning whereby the same processes are at work scale by scale across the whole scaling range…”
Section: Some Considerations For Numerical Modellingmentioning
confidence: 99%
“…The comparison suggests a new way of testing models against observations, in a way that incorporates the energy and mass transfers on all scales, which in this case seem to be inadequate quantitatively. Stolle et al (2009) have recently performed extensive studies of the horizontal scaling in ECMWF reanalyses.…”
Section: Some Considerations For Numerical Modellingmentioning
confidence: 99%
“…In this paper we therefore often use C 1 and α to reduce the characterization of the scaling (via the exponents K(q)) to manageable proportions. In any event, we show that over significant ranges of scale, the data display 'Levy collapses' when the moments are normalized by the theoretical universal K(q), and this even for scales somewhat outside the scaling range (see Stolle et al (2009) and section 5 below). In other words, the universality relation Eq.…”
Section: Spatial Cascadesmentioning
confidence: 99%
“…Recently the deterministic and stochastic approaches have been shown to be surprisingly compatible. Stolle et al (2009) analysed both meteorological reanalyses (European Centre for Medium range Weather Forecasting's (ECMWF) reanalysis (ERA40)) and meteorological forecasting models ((Global Forecast System (GFS) and Global Environmental Multiscale (GEM)) and showed that the spatial statistics of the turbulent fluxes associated with the temperature, zonal wind and humidity were indeed very close to those predicted by cascade models with deviations typically < ± 1% over the range of 5000 km down to the model/reanalysis (hyper) viscous dissipation scales. Lovejoy and Schertzer (2011) found similar results for the ECMWF interim reanalysis products, extending these results to the geopotential height, to the vertical wind, and to the meridional wind fields as well as the corresponding turbulent fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation